SELF-EFFICACY ANALYSIS OF STUDENTS' MATHEMATICAL PROBLEM-SOLVING ABILITY IN ABSOLUTE VALUE EQUATIONS MATERIALS - Fitria Handayani; Yulyanti Harisman; Armiati Armiati (Universitas Negeri Makassar, 2022)
Participants can profit from the ability to solve issues by first understanding them, then choosing the best technique, and then applying it to problems in both mathematical and non-mathematical situations. Many variables contribute to students' inability to answer mathematical questions, one of which is a lack of confidence in their abilities. The purpose of this study is to describe how well-equipped pupils are to deal with arithmetic challenges associated with absolute value equations. Study participants were selected from each level after each level's self-efficacy was assessed using questionnaires. The tools used in data collection procedures, which are training tactics, include short interviews, self-efficacy questionnaires, and assessments of one's ability for solving mathematical problems. The data processing and analysis process have three stages: data reduction, data presentation, and conclusion-making. The research subjects were three students from each of the three self-efficacy levels—very high, high, and medium—and their propensities for resolving mathematical puzzles were then evaluated. Students with a very high level of self-efficacy perform mathematical problem-solving tasks more effectively than students with high and medium levels of self-efficacy.